Risk correlates of acute respiratory infections in children under five years of age in slums of Bankura, West Bengal - Gupta, Avisek; Sarker, Gautam; Pal, Ranabir (Indian Journal of Child Health, 2014)
Background: Acute respiratory infections (ARI) are the leading cause of mortality and morbidity globally inchildren under five years of age. Objective: To find out prevalence and risk factors of ARI among under fivechildren. Methods: A population based analytical cross-sectional study was conducted in the urban slums ofBankura, West Bengal on the prevalence of ARI and feeding practices, nutrition and immunization among 152children under five years of age. Results: Overall prevalence of ARI was 44.73 percent; 43.47 percent male and45.78 percent female were affected with ARI; half of the infants suffered from ARI (51.21%), it was 45.71percent in 13- 24 months age groups; with increasing age, prevalence of ARI gradually decreased. ARI was seenin 45.76 percent of exclusively breast fed children and 57.89 percent in children with breast feeding less than sixmonths; in bottle fed children ARI prevalence was 47.82 compared to 44.18 percent in breast-fed. Risk of ARIis almost equal in normal participants and undernourished children. ARI cases were seen among 38.73 percentof completely immunization in comparison to 80.00 percent of partially-immunized children (X2=4.97,p=0.026). Conclusion: The present study had identified a high prevalence of ARI in children less than fiveyears of age. In our study population, ARI was significantly associated with immunization status, but not withfeeding practices and nutritional status of the child.